ANALISIS PENGELOLAAN PARIWISATA HALAL DI DESA TETE BATU KABUPATEN LOMBOK TIMUR NUSA TENGGARA BARAT - Budi Witarto, Arief; Trishuta Pathiassana, Mega (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
The choice of NTB as one of the halal tourism destinations in Indonesialed to the passing of Perda No. 2 of 2016 concerning Halal Tourism in NTB.The implications of this regional regulation have been widely implemented. One of them is withmany emergence of halal tourism villages, especially on the island of Lombok. This researchaims to find out in detail the management of tourism in the Tete halal tourism villageBatu in East Lombok Regency which is one of the halal tourism destinationsNTB. This study uses a qualitative approach where the sample is selected bypurposive sampling. Data collection techniques using observation, interviews, anddocumentation. The data obtained were analyzed using three pathways, namely reduction,presentation of data, and drawing conclusions made at the time of data collectiontake place. The validity of the data was tested using the source triangulation technique. ResultThe research shows that the management of the Tete Batu halal tourism village includes:several aspects, namely planning, implementation, and supervision. 1) Deep planningthe process of tourism management in Tete Batu Village seems invisible, even more sofor tourism management which in fact has been implemented by the community alreadysince a long time ago, the concept of halal has been very thick with people's livesLombok. 2) The implementation of management is focused on the efforts made by the partiesmanagers in creating a halal brand image that is already well attached toin terms of supporting facilities for worship, providing halal food, lodging managementwith the concept of halal, and community participation in management is good enoughalthough there are still many deficiencies that must be addressed. 3) Supervisionimplemented in the form of monitoring and evaluation. The focus of supervision lies onimplementation of standardization of halal tourism and further evaluation of achievementsthe purpose of the brand image of halal tourism is to increase the number of visitstourists in NTB and more specifically in Tete Batu Village. Inner obstaclesmanagement of hala tourism in Tete Batu Village, among others, a lack of budget andHuman resources that support the development of halal tourism